HDAC1‐mSin3a‐NCOR1, Dnmt3b‐HDAC1‐Egr1 and Dnmt1‐PCNA‐UHRF1‐G9a regulate the NY‐ESO1 gene expression. Issue 3 (21st December 2012) - Cartron, Pierre-François; Blanquart, Christophe; Hervouet, Eric; Gregoire, Marc; Vallette, François M.
Abstract : The NY‐ESO1 gene is a cancer/testis antigen considered to be suitable target for the immunotherapy of human malignancies. Despite the identification of the epigenetical silencing of the NY‐ESO1 gene in a large variety of tumors, the molecular mechanism involved in this phenomenon is not fully elucidated. In two non epithelial cancers (glioma and mesothelioma), we found that the epigenetic regulation of the NY‐ESO1 gene requires the sequential recruitment of the HDAC1‐mSin3a‐NCOR, Dnmt3b‐HDAC1‐Egr1 and Dnmt1‐PCNA‐UHRF1‐G9a complexes. Thus, our data illustrate the orchestration of a sequential epigenetic mechanism including the histone deacetylation and methylation, and the DNA methylation processes. Highlights: ► NY‐ESO1 is a cancer/testis antigen. ► NY‐ESO1 expression is considered to be suitable targets for the immunotherapy. ► NY‐ESO1 is epigenetically silenced in several cancers (glioma and mesothelioma).